Lermontov’s Texts in Tchaikovsky’s Oeuvre - Zivar M. Guseinova (Современные проблемы музыкознания)
Tchaikovsky’s musical legacy includes only two works related to Lermontov’s poetry. These are the song The Love of a Dead Man (1878), which is a part of Opus 38, and the a cappella chorus A Golden Cloud Spent the Night (1887). But there is information available about the composer’s other plans to compose music associated with Lermontov, manifested, in particular, in his intention to write the opera Bela to a libretto by Anton Chekhov. In both completed works, Tchaikovsky was not independent in his choice of texts, but the compositions were set to poems offered to him by other people. The song and the chorus are not equal to each other in their artistic significance: the song, unusual in its artistic solution, figuratively and intonationally connected with the characters of a few separate operas, becomes an special culmination in Opus 38; the chorus, on the contrary, is devoid of any expressive theme or interesting textural and harmonic features that distinguish the composer’s works, remaining merely a small example of the composer’s choral writing.